Coding sequences for vasoactive intestinal peptide and PHM-27 peptide are located on two adjacent exons in the human genome. - Bodner, M (1985)
The human precursor gene for vasoactive intestinal peptide (VIP) and PHM-27, a peptide that has an NH2-terminal histidine and COOH-terminal methionine amide and is closely related in sequence and activity to VIP, was detected with synthetic oligodeoxynucleotide probes. These specific hybridization segments were constructed according to the neuroblastoma VIP cDNA sequence and contained up to 39 bases. The gene structure was partly deduced by hybridization to synthetic oligodeoxynucleotide probes and partly by direct chemical nucleotide sequencing. Four exons were discovered thus far; among them are two short exons separated by a 0.75-kilobase DNA stretch, one encoding PHM-27 and the second encoding VIP (exons 1 and 2). Each of these two exons encodes both the hormone amino acid residues as well as the post-translational processing signal sequences. The 3' splice sites of the two exons contain an identical stretch of nine nucleotides. At the cDNA level, the 3' splice sites contain the same stretch of six nucleotides, which are identically spliced. The occurrence of VIP and PHM-27 coding sequences on two separate exons of the human genome and the homology of their 3' splice site may allow alternative RNA processing as discussed below.